2020
DOI: 10.1038/s41598-020-75864-2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a non-stochastic two-field hypothesis for persistent skin cancer risk

Abstract: With recurring carcinogen exposures, individual tumors develop in a field of genetic mutations through a stepwise process of clonal expansion and evolution. Once established, this “cancer field” persists in the absence of continued carcinogen exposures, resulting in a sustained risk for cancer development. Using a bioimaging approach, we previously demonstrated that a dermal premalignant field characterized by inflammatory angiogenesis persists following the cessation of ultraviolet light exposures and accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…28 In addition, dermal senescent cells produce senescence-associated secretory phenotype, which triggers angiogenesis and inflammation surrounding the cells, leading to the production of more dermal senescent cells and an environment suitable for continued carcinogenesis. 37 This could potentially explain the hyperemic expansion noted in the previous study. 28 Importantly, this also identifies a need for noninvasive imaging of subclinical lesions, as it has now been shown that tumorigenic expansion can continue in individuals no longer exposed to UV-B radiation.…”
Section: Pro -Infl Ammatory Cue S In Tissue Microenvironmentsmentioning
confidence: 82%
See 4 more Smart Citations
“…28 In addition, dermal senescent cells produce senescence-associated secretory phenotype, which triggers angiogenesis and inflammation surrounding the cells, leading to the production of more dermal senescent cells and an environment suitable for continued carcinogenesis. 37 This could potentially explain the hyperemic expansion noted in the previous study. 28 Importantly, this also identifies a need for noninvasive imaging of subclinical lesions, as it has now been shown that tumorigenic expansion can continue in individuals no longer exposed to UV-B radiation.…”
Section: Pro -Infl Ammatory Cue S In Tissue Microenvironmentsmentioning
confidence: 82%
“…The biological origins of carcinogenesis field expansion can be explained by multiple factors, including acquired mutations in p53 as discussed previously, the influence of dermal senescent cells within the hyperemic foci, and the tumour immune microenvironment associated with vasculature alterations and inflammation 12,34–36 . The influence of dermal senescence and genetic mutations plays an important role in the setting of continued tumorigenesis after the cessation of exogenous stimuli 37 . It was shown that p53 + clones were focused within the dermal hyperemic foci, suggesting that tumour growth following initial genetic mutations can continually expand after cessation of extrinsic carcinogenic treatment in areas of increased vascularity 28 .…”
Section: Pro‐inflammatory Cues In Tissue Microenvironmentsmentioning
confidence: 99%
See 3 more Smart Citations